Lebaran Rituals and Consumption Pattern: An Exploratory Study in South jakarta - Assilmi, Najwa; Fachira, Ira (Journal of Business and Management, 2014)
Purpose- Lebaran is a religious celebration for Muslims all around the world. Each year in Indonesia, which is the home of the biggest Muslims in the world, Lebaran has become a major phenomenon that is affecting the Indonesia’s retail and economic condition. The purpose of this research is to examine how Lebaran rituals affect consumers’ consumption as shown in feasting ritual as part of Lebaran. This exploratory study examines three different groups: people who are hosting the Lebaran feast, people who visit, and people who do both. Design/Methodology/Approach- A quantitative research was done with distributing questionnaire to a total of 120 samples of married South Jakarta female with children. A descriptive analysis was conducted to compare the different result of the three different groups. Findings- The majority of all three groups spent 25% more on Lebaran month rather than their regular month. The host & guest group seems to spent more spendings on main feast than those from the host only the guest only group. For main feast, most decision maker are done by the mother alone. Most respondents from all three group also choose to shop main feast at Supermarket rather than traditional market. The shopping information was get from their own peers rather than traditional media. The variance of product is the most important attributes to a store according to all three groups. For small feast, the majority of customers choose to purchase their food rather than made it themselves. The spendings from those from the host group and host & guest group is more than those who are guest only. The majority from all three groups purcOhase their food through their friends rather than special order or the supermarket. The shopping information was also mostly from their peers. The shopping attributes priority was similar to the main feast, which is the variation of product. This result shows that the customer’s social circle become an highly influential source for shopping for Lebaran. Research Limitations- This research is intended to explore the behavior of consumers and their consumption prior to Lebaran day. Due to the limitation of time and resource the sample taken might not represent the whole Indonesian behavior. The generality of the findings are limited to a certain area in South Jakarta. Practical Implications- Business owner can take benefit by starting a more personal marketing mix starting at the mother’s social circle. The availability of a product also needs to become a priority for customers on Lebaran. Originality/Value- This study is applied in Indonesia which Islam is the majority religion but also a country who hold many traditional rituals. The topic is the Lebaran phenomenon which is  a fuse between traditional culture and religious activities to find out the consumption tendencies of different type of Indonesian customer constitute the originality of this study.Keywords: marketing